The impact of land use landscape pattern on river hydrochemistry at multi-scale in an inland river basin, China - Junju Zhou; Chuyu Luo; Dongfeng Ma; Wei Shi; Lanying Wang; Zhaonan Guo; Haitao Tang; Xue Wang; Jiarui Wang; Chunfang Liu; Wei Wei; Chunli Wang (Ecological Indicators, 2022)
The impact of the land use landscape pattern on river hydrochemistry has significant scale effects. It is the premise and foundation of landscape optimization and the conservation of water resources to accurately identify the core scale of the landscape pattern impacting on river hydrochemistry. Taking Binggou River Basin in the source region of Shiyang River Basin as the study area, this paper selected the three spatial scales of catchment area, buffer zone, and riparian zone, and the relationships between land use types and landscape indices and river hydrochemical characteristics were analyzed at different spatio-temporal scales using redundancy analysis. The results showed that the hydrochemistry characteristics of Binggou River Basin had strong temporal variability, and the rainy season was the key period when the land use landscape pattern affected the river hydrochemistry. The sub-watershed and riparian scales were the core scales of influence of the landscape pattern on river hydrochemistry in Binggou River Basin. In particular, the landscape pattern index contributed the most to the river hydrochemistry at the sub-watershed scale on the whole, which was the core scale affecting river hydrochemistry. The “source” or “sink” functions of the same land use type also changed as the scale changed. Forest land showed weak “source” effect at the sub-watered scale, but a strong interception effect on the soil erosion process at the riparian scale, which is a typical “sink” landscape.